Lukas Geniušas performs Prokofiev's Piano sonata no. 7 - Prokofiev, Sergey 1891-1953 (Telmondis - Münchner Philharmoniker, 2017)
Silver medalist of 2015 Tchaikovsky Competition, Lukas Geniušas has been praised for his "agonizing search for a performance style that is fully modern and catching the spirit of the age" (Kommersant Russia). The outstanding young talent performs Prokofiev's Piano Sonata No. 7 as part of the 2016 MPHIL 360°. For the 2016 MPHIL 360° festival, Valery Gergiev and the Münchner Philharmoniker put together a musical celebration of impressive proportions! The three-day festival put a special focus on Sergei Prokofiev's piano sonatas performed by honorees of the International Tchaikovsky competition
Keywords: Sonatas (Piano); Internet videos